2000
DOI: 10.1111/j.1572-0241.2000.01931.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive antigen-based assay for assessing Helicobacter pylori eradication: a European multicenter study

Abstract: HpSA has proven to be a useful method in posttreatment eradication testing for H. pylori. Its ease of use, speed, and noninvasive nature make HpSA testing an ideal method for post-treatment monitoring where a second EGD may not be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 11 publications
4
65
1
Order By: Relevance
“…6 We have also used the same cut-off values of optical density as were adopted by the authors of the largest European study performed to monitor eradication therapy. 23 In the light of this, it is difficult to understand the discrepancy between the results of this European study and ours. It must be taken into account, however, that the former was a multicentre study, whereas our investigation was conducted in a single centre.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…6 We have also used the same cut-off values of optical density as were adopted by the authors of the largest European study performed to monitor eradication therapy. 23 In the light of this, it is difficult to understand the discrepancy between the results of this European study and ours. It must be taken into account, however, that the former was a multicentre study, whereas our investigation was conducted in a single centre.…”
Section: Discussioncontrasting
confidence: 50%
“…Although some investigators have demonstrated that UBT and HpSA are absolutely equivalent in terms of sensitivity and specificity in the evaluation of eradication therapy, 15,23,24 others have documented a lower than expected reliability of HpSA in this setting. [25][26][27][28][29] It has been rightly emphasized that many studies on the performance of HpSA in post-treatment assessment have used UBT as the gold standard, and this has certainly diminished the meaning of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Positive and negative control wells did not initially reveal spectrophotometric reading within expected ranges; the problem was corrected by rinsing the wells seven times instead of four times between steps, a modification recommended by the manufacturer. Some investigators have deemed HpSA optical density (OD) values above 0.160 to be positive, values between 0.140 and 0.159 to be indeterminate, and values below 0.140 to be negative (27). We considered values equal to or above 0.140 to be positive in accordance with a calculated optimal cutoff point (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have recently shown that the Premier Platinum H. pylori stool antigen test kit (HpSA) (Meridian Diagnostics, Inc) is comparable to other noninvasive tests for initial diagnosis of H. pylori infection (2,4,11,12,13,26,28). For monitoring the efficacy of eradication treatment, however, the results have been equivocal (11,13,26,27,28). By comparing HpSA test results to endoscopy and UBT findings, we attempted to confirm the validity of HpSA for diagnosis and to establish the long-term posttreatment follow-up in patients in a developing country where there is a very high prevalence of H. pylori infection.…”
mentioning
confidence: 99%
“…In that case, only highly accurate tests (with very high specificity) are acceptable and serology will soon not be suitable anymore. Urea breath tests 231 232 and stool antigen tests [233][234][235] may be valuable alternatives. Screening for H pylori will provide one of two possibilities: a positive test result or a negative test result.…”
Section: Rationale and Limitations Of The Various Approaches Of The Dmentioning
confidence: 99%